2008
DOI: 10.4141/cjss06005
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide emissions from denitrification and the partitioning of gaseous losses as affected by nitrate and carbon addition and soil aeration

Abstract: . 2008. Nitrous oxide emissions from denitrification and the partitioning of gaseous losses as affected by nitrate and carbon addition and soil aeration. Can. J. Soil Sci. 88: 133Á143. National inventories of N 2 O emissions from agricultural situations are being developed; however, the factors controlling such emissions may vary with soil and environmental conditions and management practices. This study determined the relative importance of soil aeration, as measured by water-filled pore space (WFPS), NO , N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
66
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(80 citation statements)
references
References 53 publications
12
66
2
Order By: Relevance
“…This is consistent with other studies that found NO 3 levels greater than 5 to 10 mg N kg -1 did not limit N 2 O production (Ryden, 1983;Gillam et al, 2008). It appeared over-winter soil conditions favored the use of NO 3 by facultative anaerobes as a terminal electron acceptor.…”
Section: Water Extractable Organic Carbon Nitrate and Over-winter Nsupporting
confidence: 82%
See 2 more Smart Citations
“…This is consistent with other studies that found NO 3 levels greater than 5 to 10 mg N kg -1 did not limit N 2 O production (Ryden, 1983;Gillam et al, 2008). It appeared over-winter soil conditions favored the use of NO 3 by facultative anaerobes as a terminal electron acceptor.…”
Section: Water Extractable Organic Carbon Nitrate and Over-winter Nsupporting
confidence: 82%
“…5a) [2013][2014]. This is consistent with other studies that have shown that N 2 O production was limited by NO 3 in low NO 3 soils and mineralizable C in high NO 3 soils (Weier et al, 1993;Gillam et al, 2008;Mitchell et al, 2013).…”
Section: Water Extractable Organic Carbon Nitrate and Over-winter Nsupporting
confidence: 82%
See 1 more Smart Citation
“…This is consistent with denitrification being the primary source of N 2 O emissions. Similarly, other field and laboratory studies within this region provided evidence that N 2 O emissions from agricultural soils are associated primarily with denitrification Gillam et al 2008;Zebarth et al 2008). for the denitrification process becomes limiting .…”
Section: Discussionmentioning
confidence: 99%
“…Soil NO 3 ( availability, aeration, and carbon availability are commonly identified as important factors controlling N 2 O emissions and denitrification (Knowles 1982;Weier et al 1993;Granli and Bøckman 1994;Gillam et al 2008). Soil water content is a major determinant of soil aeration through its effect in displacing the air-filled pore space.…”
mentioning
confidence: 99%